Assessment of the incidence of leukemia virus (BLV) in cattle in the Republic of Dagestan using PCR diagnostics - D. A. Baboshko; K. A. Elfimov; M. G. Daudova; Kh. G. Koychuev; Kh. F.‐K. Gapizova; N. M. Gashnikova (Юг России: экология, развитие)
Aim. Assessment of the incidence of leukemia virus in cattle using PCR diagnostics in herds of the Republic of Dagestan and study of the molecular genetic characteristics of circulating viruses.   Materials and Methods. 150 cattle blood samples were examined. PCR diagnostics of samples for the presence of bovine leukosis virus (BLV) were carried out using the RealBest‐Vet DNA BLV test system and a laboratory set of primers. Some of the samples were sequenced using the Sanger method and their phylogenetic analysis was performed.   Results. Out of 150 samples, 24 samples were positive for the presence of BLV. In the Untsukulskiy district, no BLV DNA was detected in any of the 16 samples. In the Karabudakhkentskiy district out of 40 – in 2 (5 %), in Buynakskiy district – in 1 out of 30 (3.3 %) and in Babayurtovskiy district–in 21 out of 60 samples BLV was detected (35 %). For 13 BLV‐positive samples, fragments of the env gene measuring 1000 bp were obtained and deciphered. According to phylogenetic analysis, 7 samples of BLV belong to the 7th, and 6 – to the 4th genotype of BLV. The BLV genotype 4 isolated in the Babayurtovskiy district clusters with viruses from Kazakhstan, while viruses of genotype 4 from other farms cluster with Russian BLV. The studied samples of genotype 4 did not form common clusters. For the BLV genotype 7 isolated in farms of the Babayurtovskiy district, on the contrary, a combination of sequences into one cluster of genetically similar viruses was observed.   Conclusion. Significant differences in the incidence of leukemia virus in livestock on farms in Dagestan were revealed. No patterns were found in the registration of cattle cases with a specific breed of cattle or with the age of the animal. It has been shown that viruses of both genotypes 7 and 4 circulate in the Republic. For BLV 4, it is assumed that there are different ways of its introduction into farms but no associated chains of virus spread have been found. For BLV genotype 7, transmission of BLV has been registered, which indicates the need to strengthen leukemia prevention measures on farms.